Regulated intracellular ligand transport and proteolysis control EGF signal activation in Drosophila. - Lee, JR; Urban, S; Garvey, C; Freeman, M (2001)
The membrane proteins Star and Rhomboid-1 have been genetically defined as the primary regulators of EGF receptor activation in Drosophila, but their molecular mechanisms have been elusive. Both Star and Rhomboid-1 have been assumed to work at the cell surface to control ligand activation. Here, we demonstrate that they control receptor signaling by regulating intracellular trafficking and proteolysis of the ligand Spitz. Star is present throughout the secretory pathway and is required to export Spitz from the endoplasmic reticulum to the Golgi apparatus. Rhomboid-1 is localized in the Golgi, where it promotes the cleavage of Spitz. This defines a novel growth factor release mechanism that is distinct from metalloprotease-dependent shedding from the cell surface.